Malawi Soil Profile Data – Malawi Land Resources Evaluation Project, 1987 to 1991 - Ministry of Agriculture, Government of Malawi; United Nations Development Program; Food and Agriculture Organization of the United Nations (International Food Policy Research Institute, 2021)
The Land Resources Evaluation Project (LREP), which ran from 1988 to 1992, was a joint government of Malawi, United Nations Development Programme (UNDP), and Food and Agriculture Organization (FAO) project that involved a close reconnaissance of the agro-ecological resources of Malawi. Extensive fieldwork was done to map the soils across the country at the moderately detailed scale of 1:250,000 (1 cm = 2.5 km). Weather data were analyzed to generate averages for various indicators for use in mapping the agro-climatological zones of Malawi at the same geographic scale. The soils and agroclimatic maps developed were then overlaid to develop a ‘land unit’ map for Malawi. Each land unit is defined by a unique combination of relatively homogeneous soil and climate properties within its boundaries. These land units were then used with information on the optimal soil and climate conditions for growing a range of rainfed agricultural crops, as well as irrigated rice and tree species, to undertake a spatial suitability analysis for the production of each in each land unit. The soil survey mapping involved examining soil profiles from several thousand locations across the country between November 1987 and September 1991. The soil surveyors recorded information on the soil profiles and on individual horizons within the soil profiles on standard forms while they were in the field. The data collection forms in paper format were then archived by the Land Husbandry Branch (later renamed Land Resources and Conservation Branch). Soil samples were also collected for chemical analysis. Key professional personnel involved in the collection of the soil profile data included J.A. Eschweiler, S.J. Nanthambwe, S. Paris, J.H. Venema, A.J.M. Lorkeers, R.I. Green, A.E. Kandodo, P. Banda, Mr. Chikowi Digital records of the soil profile data were not created under the LREP-Malawi project. In 1999, members of the Maize Commodity Team at Chitedze Agricultural Research Station, led by Todd Benson, created digital files of the LREP soil profile and horizon data from the paper field data forms. The majority of the data entry was done by Sophie C. Nambuzi, with assistance from Ivy Ligowe and Maction Komwa. The efforts of the team were generously assisted by Mr. Stephen J. Nanthambwe of the Land Resources and Conservation Branch, who was a participant in the original soil sampling exercise.